Clinical Profile of Dengue Fever in Children - Alam, ABM Shahidul; Sadat, S Anwar; Swapan, Zakaria; Ahmed, Aftab U; Karim, Md Nazmul; Paul, HK; Zaman, Sanjana (Bangladesh Journal of Child Health, 2010)
Background: Dengue infection has become endemic in Bangladesh since it has been broken out in June 2000. Although children are the usual victim of dengue infection, there is paucity of published data regarding dengue infection in children in our country. Objectives: This study was designed to document the presenting features and outcome of Dengue infection in children. Materials and Methods: This cross sectional study was done among the children having Dengue infection. Fifty four consecutive patients were enrolled. Purposive sampling was done. In every patient a detailed history was taken. Clinical examinations and relevant investigations were done. Data were collected in a predesigned structured questionnaire. Data were analyzed with the help of descriptive statistics and Chisquare (x2) Test. Results: The mean age of the patients was 6.5±3.5 years with equal male and female ratio. Among 54 patients, 40.7% presented with dengue fever (DF), the rest (59.3%) presented with dengue haemorrhagic fever (DHF). Most of the patients presented with high grade continued type of fever (75.9%), followed by abdominal pain (59.3%), vomiting (57.4%). Itchy rash and fever were the most important characteristic signs (75.9% each). Flushed appearance observed in 68.4% and 59.3% patients showed bleeding manifestation of which sub-conjunctival haemorrage was the commonest form (33.3%). Leucopenia were present in only 9.3% of the patients. Platelet count less than 100×109/L were found in 68.5% patients. Tourniquet test was positive in 31.5% of cases. All of the patients had packed cell volume (PCV) less than 45%. Raised serum alanine aminotransferase (ALT) was observed in 40.7% of children. IgM and/or IgG antibodies for dengue virus were positive in 96.29% patients. Majority (94%) of the patients completely recovered from the disease and only 6% died. Conclusion: High grade continued fever, vomiting with abdominal pain and itchy skin rash (with normal platelet count) were the presenting features. Commonest form of bleeding manifestation was subconjunctival haemorrhage. Bleeding manifestation had a significant association with the degree of thrombocytopenia but no corelation was observed with tourniquet test positivity. Key words: Dengue fever (DF); dengue haemorrhagic fever (DHF); paediatric. DOI: 10.3329/bjch.v33i2.5678 Bangladesh Journal of Child Health 2009; Vol.33(2): 55-58